Nearly-zero energy buildings: cost-optimal analysis of building envelope characteristics - Loukaidou, K.; Michopoulos, Apostolos; Zachariadis, Theodoros (My University, 2017)
Energy consumption in the building sector continues to increase in the entire world and therefore, the determination of costoptimal solutions towards nearly zero-energy buildings is a serious challenge. The present study is focused on the optimal thermal features of the building envelope, including thermal insulation on wall, roof and ground floor as well as the optimal window properties, in order to achieve nearly-zero energy buildings in the climate conditions of Cyprus. A systematic and robust scientific procedure was adapted in order to determine levels of energy performance leading to minimum life-cycle cost. Energy simulations of different reference test-cell buildings were performed, based on the external envelope’s surface to total building volume ratio, and the cost-optimal performance levels were calculated in accordance with Regulation 244/2012/EU, taking into consideration three different climate areas of Cyprus – the cities of Limassol and Nicosia and the mountainous area of Saittas. Both the optimal thermal transmittance coefficient of the external envelope elements and the optimal window properties for each reference test-cell building were calculated. The results demonstrate that the cost-optimal energy performance levels of reference test-cell buildings in Cyprus are considerably higher than the national minimum requirements. Moreover, a linear correlation was found between the optimal (mean) thermal transmission coefficient and the study area, a result that underlines the necessity of forming three independent climate zones in Cyprus instead of one that exists today.
Keywords: Nearly Zero Energy Building (nZEB);; Building envelope; Cost-Benefit analysis; Thermal insulation; Glazing properties; EnergyPlus